Lexical-intonational expression structure of irrational states as a prediction of one’s own way in the poetic collection of Vasyl Stus “Palimpsests” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article communicates the mythology of Vasyl Stus and lexical-intonational features of its expression. The analysis is carried out based on the irrational states, and is expressed in the chronotope of dreams. The mythological thinking of the poet was proved in the process of analysing the poems of the collection, due to the active use of the author’s word formation, demonstration of oxymoronic thinking in determining important categories of life, time and space, etc. It has also been found that the manifestation of creative intuition as an inner force is embodied in the poet’s mythological reconstruction of his own way of life, which he intuitively felt as a correlative pair to Golgotha of the Savior. The outline of Christian initiations is determined, according to which V. Stus foresaw and described his way. Dramatically sharpened perception of the world affected the intonation syntactic features of the poet’s poetry. Fragile and impulsive rhythm, intonation ups and significant pauses, elliptical constructions, gradations, amplified by anaphora, convey psychological states associated with the semantics of wailing, breaking hands, cracks. These lexical and intonational means determine the irrational basis of V. Stus’ poetry. Intensive word formation by V. Stus, variants of tokens to characterize the key image of the collection confirm that palimpsests are the main principle of the author’s text formation.
Keywords: intuitive self-comprehension; transcendence; path mythology; gradation; oxymoron